Food intake and thermic effect of feeding in thyroid-deficient pigs - Macari, Marcos [UNESP] (Elsevier, 1984)
Short and long-term thyroidectomy and Methimazole treatment reduced food intake in young growing pigs. The thermic effect of feeding assessed by the increment in rectal temperature after the beginning of food ingestion was reduced in thyroidectomized animals, but no effect could be observed in Methimazole-treated pigs. Propranolol injection after short-term treatment decreased food intake in sham-operated and treated animals, but reduced the thermic effect of feeding only in the thyroidectomized and Methimazole-treated pigs. Long-term treatment inhibited the effect of propranolol in reducing food intake and the thermic effect of feeding. On the basis of these data, it was suggested that the interaction between thyroid hormones and catecholamines (noradrenaline) plays an important role in the regulation of food intake and in the thermic effect of feeding in thyroid-deficient pigs.
Keywords: catecholamine; propranolol; thiamazole; thyroid hormone; animal experiment; body temperature; endocrine system; food intake; hypothyroidism; nonhuman; rectum temperature; swine; thermogenesis; thyroidectomy; Animal; Body Temperature; Eating; Female; Male; Methimazole; Norepinephrine; Propranolol; Support, Non-U.S. Gov't; Swine; Thyroid Hormones; Thyroidectomy